Uso de imagens como estratégia de ensino-aprendizagem em Educação Ambiental - ROCCO, NERIELLY ELIZABETH DE (2022)
As educators and students, we experience constant questions about our interactions with the environment that surrounds us, but we understand that many of these interactions result in the emergence of complex socio-environmental problems, comprising natural, social, economic, political and cultural components, inside or outside the teaching environment. In this way, Environmental Education (EE), as a field of knowledge capable of problematizing and transforming the relationships established between society and nature, also aims to promote reflective and educational actions on the socio-environmental challenges and problems faced. There are different educational instruments capable of helping EE practices, such as dynamics, the use of films, the application of workshops, the use of games. Among these, the use of images stands out, devices that can provide information about ways of reading and rereading the environment that surrounds us. Thus, this research aimed to investigate and contextualize the socio-environmental problems experienced by society, in addition to contributing to a citizen education of students at a State College in Guarapuava, Paraná. A didactic and technological instrument was also built, which could assist in the understanding of the local environment (municipality) and expand the reflections of the natural, historical, social, economic, political and cultural scope of the global environment. As a research methodology, participatory research was adopted, using the questionnaire, the field diary and the focus group as research instruments. We found that at the beginning the students had a naturalistic conception of the environment and their actions in the face of socio-environmental problems were considered conservative and pragmatic, however, with the application of the workshops this position and the way of acting on environmental issues were expanded. In addition, we realized the need to build a didactic instrument with the images, discussed and socialized, so that other students and teachers could also perceive the environment that surround them in a more critical and contextualized way. The product developed here was a Scrapbook, entitled “Socio-environmental Reflections on the Local Environment” and the participants of this research contributed with some reflections of this material. In this way, the scrapbook proved to be a great didactic and pedagogical tool capable of implementing the practice of EE in formal spaces, contributing to the approximation between educators and students, it also provided a critical formation of these in the face of socio-environmental problems, thus providing subjects more active in society.